Challenges of Law Enforcement against Domestic Violence Between Regulation and Implementation - Kurniadi, Wahyu (Siber International Journal of Advanced Law (SIJAL), 2024)
This article examines the challenges of law enforcement in handling domestic violence (DV) cases in Indonesia. Despite the enactment of Law No. 23 of 2004 on the Elimination of Domestic Violence, implementation remains hindered by multiple obstacles, including limited understanding and gender sensitivity among law enforcement officials, insufficient victim protection facilities, and prevailing patriarchal cultural norms that discourage reporting. Data analysis shows that psychological violence is the most prevalent form, followed by physical, sexual, and economic violence, indicating the need for a broader approach beyond physical abuse. Through a normative juridical method supported by empirical data, this study finds that legal frameworks alone are insufficient without strong institutional commitment and community awareness. The findings highlight the urgency of strengthening victim support systems, enhancing legal officers’ capacity, and promoting public education to foster a culture of zero tolerance for DV. The article concludes that an integrated strategy involving government, law enforcement, civil society, and communities is essential for effective law enforcement and the protection of DV victims. This research contributes to the ongoing discourse on improving justice and protection mechanisms for vulnerable groups, particularly women and children, within the domestic sphere.